Application of Wittgenstein’s Sprachspiel in Speaking English Teaching: A Linguistic Philosophical Perspective of Speaking English Teaching for Non-English Major Graduate Students in China - Jing , Hua (Journal of English Language Teaching and Applied Linguistics, 2021)
“Sprachspiel(Language Game)”, a language philosophical term proposed by Wittgenstein, indicates that the meaning of language is in the use of language in all kinds of language games. This concept helps to transfer our focus from abstract language analysis to practical language uses, which throws a light on college English teaching in China. Based on this language philosophical point of view, this paper intends to have some practices on speaking English teaching for non-English major graduates. Based on the analysis of the difficulties and problems of the target students’ English learning, this paper puts forward some tentative ways for speaking English teaching in large class. The experimental teaching of a whole school year proves that this new teaching mode enhances students’ interests in English and improves students’ studying method as well as their Speaking English level. From the survey result, it finds out that this paper also makes an analysis of the surveys conducted both at the very beginning and the end of the school year.